Racial and socioeconomic disparities in patient experience of clinician empathy: a protocol for systematic review and meta-analysis. Issue 6 (28th June 2020) - Roberts, Brian W; Trzeciak, Christian J; Puri, Nitin K; Mazzarelli, Anthony J; Trzeciak, Stephen
Abstract : Introduction: Clinician empathy is a vital component of high-quality healthcare. Healthcare disparities may reflect a societal lack of empathy for disadvantaged persons in general, and recent research suggests that socioeconomic disparities exist in patient satisfaction with clinicians. However, it is currently unclear if there are disparities in patient experience of empathy from clinicians. Our objective is to systematically analyse the scientific literature to test the hypothesis that racial and socioeconomic status (SES) disparities exist in patient-reported experience of clinician empathy. Methods and analysis: In accordance with published methodological guidelines for conducting a systematic review, we will analyse studies reporting patient assessment of clinician empathy using the Consultation and Relational Empathy (CARE) measure, which to date is the most commonly used and well-validated methodology in clinical research for measuring clinician empathy from the patient's perspective. We will use a standardised data collection template and assess study quality (risk of bias) using the Newcastle-Ottawa Scale. We will abstract data for the CARE measure stratified by race and SES, and we will contact the corresponding authors to obtain stratified data by race/SES if not reported in the original manuscript. Where appropriate, we will pool the data and perform quantitative meta-analysis to test if non-white (compared to white) patients and low SES (compared to high SES) patients report lower scores for clinician empathy. Ethics and dissemination: No individual patient-level data will be collected and thus the proposed systematic review does not require ethical approval. This systematic review will test if racial and SES differences exist in patient experience of clinician empathy, and will inform future research to help promote healthcare equity. PROSPERO registration number: CRD42019142809.